(untitled) (Journal of Environmental Microbiology and Toxicology, 2024)
This 60-day study investigated the use of poultry manure (PM) at 10% w/w to drive crude oil elimination in impacted soil at a loading contaminant concentration of 5% v/w. Gas chromatography determined removal efficiency while the bacterial community was analysed using standard microbiological techniques. The presence of crude oil as a contaminant made the soil more alkaline and reduced its nutrient content across the board. The addition of PM improved soil nutrient properties and brought soil pH closer to neutral. PM amendment resulted in total petroleum hydrocarbon elimination levels of 96.83%. The total heterotrophic bacterial (THB) and hydrocarbon utilising bacterial (HUB) abundance in the PM-treated soils showed a steady rise till day 40 with values of 7.93 Log CFU/g and 8.83 Log CFU/g respectively, after which mean counts dropped. Statistically significant differences at 95% confidence interval (p≤0.05) in TPH elimination were seen between the control studies and the PM-treated soil. THB and HUB counts also differed significantly (p≤0.05) between the unpolluted control and the PM treatment study but no statistically significant differences were obtained between the PM-treated soil and the polluted control. Bacterial diversity analysis revealed a predominance of Bacillus spp., Staphylococcus spp., and Micrococcus on day 0. Dominance shifted to Klebsiella pneumoniae, Bacillus, and Citrobacter spp. by the end of the study, indicating that these genera were the drivers of crude oil biodegradation during the study. The application of poultry manure effectively enhanced the biodegradation of crude oil in impacted soil.